Experimental and numerical studies on heat exchange between slag/metal particles and air inside countercurrent cyclone heat exchanger for recovering waste heat from molten slags in dry and centrifugal granulation process - Shali Lv; Yuhua Pan; Yansong Li; Ming Zhao; Yu-an Jing; Changyou Cai; Jiaqi Zhong; Jun Wang; Haixin Guo (PLoS ONE, 2026)
In dry and centrifugal granulation of molten slags with heat recovery, the heat exchange efficiency between high-temperature particles and the cold air directly determines the efficiency of waste heat recovery. However, the heat transfer characteristics between pure slag particles granulated from blast furnace slag and air and between a mixture of slag and metal particles granulated from steelmaking slag and air in complex flow fields still remain unclear. Therefore, this study employs a combined approach of experiment and numerical simulation to comparatively investigate the heat transfer behavior of pure slag particles and mixtures of slag and metal particles in a countercurrent cyclone heat exchanger. The investigation results indicate that the heat exchanger exhibits optimal heat transfer performance under specific operating conditions, with the maximum heat exchange efficiencies being 80.0% for pure slag particles and 77.0% for a mixture of slag/metal particles produced from steelmaking slag. Both experimental and numerical simulation results indicate that metallic iron particles produced from granulation of steelmaking slag lowers the heat exchange efficiency; when the metallic iron content in the slag increases from 2.5% to 10% by weight, the heat exchange efficiency drops from 77.0% to 73.0%. The numerical simulation results further reveal that the spatial distribution of particles within the heat exchanger is a key factor determining the overall heat exchange efficiency. The results provide a theoretical basis for design and operation optimization of industrial countercurrent cyclone heat exchangers for waste heat recovery from molten slags in dry and centrifugal granulation process.